Use of sigmoid colon in orthotopic neobladder reconstruction: Long‐term results. (7th September 2016) - Nicita, Giulio; Martini, Alberto; Filocamo, Maria T; Saieva, Calogero; Tosto, Aldo; Stomaci, Niceta; Bigazzi, Barbara; Villari, Donata
Abstract : Objectives: To present our experience with a sigmoid orthotopic neobladder. Methods: We retrospectively evaluated the functional and oncological outcomes of 160 patients who underwent orthotopic neobladder reconstruction using a detubularized 20–25‐cm sigmoid segment at our institution. Each patient was evaluated every 3 months the first year, every 6 months for the next 4 years and annually thereafter. Urodynamic studies of all consenting patients were carried out after 6 months, and 2, 5 and 10 years. We carried out the log–rank test, and used Cox regression models and Kaplan–Meier survival analysis. Theanova test was used to compare urodynamic findings over time. Results: Mean follow up was 6.8 years (range 0.65–21.7 years). Overall survival was 58.1% at 5 years, and 47.1% at 10 years. Early complications occurred in 36 patients (22.6%); late complications in 40 (25%). Stage V chronic kidney disease developed in two patients (1.3%). Complete (daytime and night‐time) continence, defined as no need for pads or condom devices, was achieved by 45% of patients at 5 years, daytime continence was achieved by just 36% of patients; both were unchanged at 10 years. A significant difference emerged in maximal neobladder capacity and post‐void residual values between 6 months and 2 years, and between 2 and 5 years ( P < 0.01 and P = 0.03, respectively). Conclusions: Sigmoid neobladder continence and capacity significantly improve over the first 5 years, and they remain stable over the long term. Upper urinary tract function is not affected by endoluminal pressure, and the rate of metabolic imbalance is negligible.